ENDOSCOPIC DISSECTION OF THE VESSELS WHILE ABDOMINAL LIPOSUCTION - О. V. Popova (Креативная хирургия и онкология, 2017)
Materials   of   investigations  directed  to   reduction  of   hemorrhage  in  abdominal liposuction  are  presented in the  paper. The technique of  preventive  devascularization of abdominal wall was  grounded. The opportunity of  performing video-assisted abdominal vascular dissection as the  preliminary  stage of liposuction  was  studied. The technique of surgical operation was worked  out. Efficiency of  abdominal vascular  dissection aimed at reduction of hemorrhage was investigated The technique suggested permits to obtain more than  twofold reduction of hemorrhage in abdominal liposuction.